Policy disparities in response to the first wave of COVID-19 between China and Germany - Yuyao Zhang; Leiyu Shi; Haiqian Chen; Xiaohan Wang; Gang Sun (BMC, 2021)
Abstract Objective Our research summarized policy disparities in response to the first wave of COVID-19 between China and Germany. We look forward to providing policy experience for other countries still in severe epidemics. Methods We analyzed data provided by National Health Commission of the People's Republic of China and Johns Hopkins University Coronavirus Resource Center for the period 10 January 2020 to 25 May 252,020. We used generalized linear model to evaluate the associations between the main control policies and the number of confirmed cases and the policy disparities in response to the first wave of COVID-19 between China and Germany. Results The generalized linear models show that the following factors influence the cumulative number of confirmed cases in China: the Joint Prevention and Control Mechanism; locking down the worst-hit areas; the highest level response to public health emergencies; the expansion of medical insurance coverage to suspected patients; makeshift hospitals; residential closed management; counterpart assistance. The following factors influence the cumulative number of confirmed cases in Germany: the Novel Coronavirus Crisis Command; large gathering cancelled; real-time COVID-19 risk assessment; the medical emergency plan; schools closure; restrictions on the import of overseas epidemics; the no-contact protocol. Conclusions There are two differences between China and Germany in non-pharmaceutical interventions: China adopted the blocking strategy, and Germany adopted the first mitigation and then blocking strategy; China's goal is to eliminate the virus, and Germany's goal is to protect high-risk groups to reduce losses. At the same time, the policies implemented by the two countries have similarities: strict blockade is a key measure to control the source of infection, and improving medical response capabilities is an important way to reduce mortality.